Cooperation between the People’s Republic of China and the United Nations in peacekeeping activity - Jiang Yumeng (Journal of the Belarusian State University. International Relations, 2022)
We present a theoretical and practical review of the political and legal aspects of the People’s Republic of China’s participation in the UN peacekeeping activities and China’s policy of peace on the planet Earth. We examine the political and regulatory aspects of China’s peacekeeping activity in cooperation with the UN and identify the most pressing problems.